Effect of graded levels of Jojoba meal in the complete feed of rabbits on voluntary intake and nutrient utilization (Journal of Laboratory Animal Science, 2018)
The study was conducted to evaluate the supplementation of Jojoba meal (Simmondisa Chinensis) on feed  consumption, body weight changes, feed efficiency, and digestibility of nutrients in rabbits. A total of forty  New Zealand white rabbits (4 week old) were randomly allotted to four dietary treatment groups of ten rabbits  in each group. The control group (T0) was fed with complete feed with no Jojoba oil meal and test groups  were fed complete feed with 5, 15 and 25% Jojoba oil meal in T1, T2 and T3 groups respectively. The daily dry  matter intake in test groups were significantly (P≤ 0.05) reduced as compared to the control group. The average  weekly body weight in test diet groups found significantly (P≤ 0.05) reduced consistently leading to reduction  of body weight. Digestibility of either proximate principles (Dry matter, Organic matter, Crude fibre, Nitrogen  free extractives) or fibre fractions (Neutral detergent fibre and Acid detergent fibre) was unaffected by jojoba  supplementation whereas crude protein and ether extract digestibility and intake of total digestible nutrients  and digestible crude protein were significantly lower in treated groups as compared to control group of rabbits.
Keywords: jojoba meal; rabbits; nutrients